Electrochemical performance of Nickel foam electrode in Potassium Hydroxide and Sodium Sulfate electrolytes for supercapacitor applications - Niknam, Ehsan; Naffakh-Moosavy, Homam; Ghahraman Afshar, Majid (Journal of Composites and Compounds, 2022)
Nickel foam is a shallow-density metal part with very high electrical and thermal conductivity. Nickel foam is used widely as the current collector in electrochemical energy storage. In previous research, the electrolytes used for electrodes in energy sources in the laboratory are often of the aqueous electrolyte type due to their low cost and easy access. In this study, studies were performed to identify and confirm the accuracy of nickel foam, such as scanning electron microscopy and X-ray energy diffraction spectroscopy. Then, in common electrolytes, 1 M potassium hydroxide (KOH) and 0.1 M sodium sulfate (Na2SO4) were investigated by CV, GCD, and EIS analyses. Finally, according to the data and results, the desired electrolyte can be selected depending on the type of use in different environments.